(untitled) (International Journal of Geoscience, Engineering and Technology, 2023)
This technical characterization work analyzed the possible variations of the colors of 16 samples of colored mortars for coating that were submitted to the weather in the city of Teófilo Otoni – MG and under protection of the same in a period of 21 days. Together with this analysis, its resistance to compression was also observed with the same inorganic pigments based on iron oxide with contents varying between 2% and 5%, where 60 specimens were made and broken at ages of 14 and 28 days of cure. The results of the experiments tested under compression were satisfactory after a period of 28 days, given that there was emphasis on the 1:3 mixes with the addition of 2% of inorganic red pigment, which had a higher resistance of 2.08 MPa than the reference mix, which is equivalent to 31.51 MPa. As for the 1:5 mix with the addition of 5% inorganic blue pigment, it obtained a gain of 1.03 MPa higher in terms of its compressive strength when compared to the reference mix, which is equivalent to 14.80 MPa. The visual evaluation also took place for two exceptions, where the 1:5 trace with the addition of 5% blue pigment suffered with the period that was in visual observation of the external environment. However, it is also worth noting that the 1:5 mix with the addition of 5% red pigment had its surface modified to the point of not being considered suitable for use both indoors and outdoors.